Pemberian ASI Sebagai Gizi Pelindung: Aspek Imunologi Bayi: Breastfeeding as Protective Nutrition: The Immunological Foundation for Infants - Pelangi, Bunga; Wasito, Erika; Sitorus, Nova; Shella, Shella (Universitas Airlangga, 2025)
Background: Breastfeeding, a crucial foundation for infant health, provides essential protective nutrition and a complex array of immune-protective factors. Breastfeeding as a natural, protective, and ethical practice is very important to support the health of infants and, by extension, the health of future generations. Objectives: The author emphasizes the biological components of breast milk as physiological protection for infant immunity and highlights the importance of breastfeeding promotion and protection within ideological and cultural contexts. Methods: A comprehensive literature review was performed using online database from Google Scholar to explore the immunological foundation of breastfeeding from original research articles published in recent 5 years. Discussions: Maternal health and maternal immunity are transferred to the infant through breast milk, providing a temporary but significant shield against pathogens. Ethical and philosophical dimensions of breastfeeding as an intrinsic maternal practice that extends beyond nutrition to embody intergenerational health protection. Conclusions: The role of breastfeeding as a natural, protective, and ethical practice is very important to support the health of infants and, by extension, the health of future generations. Philosophically and theoretically grounded strategies are effective in enhancing exclusive breastfeeding rates, particularly in treatments focused on breastfeeding education, empowerment, and counselling. Assistance in the initial days and weeks following delivery is crucial, as this timeframe is critical for the effective establishment of lactation.